ICT as a re-engineering strategy on claim settlement in some selected insurance companies In Nigeria: The pandemic experience - Madu Frances; Isichei Ejikeme; Vincent Onodugo (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: This study addresses the effect of ICT on the relationship between re-engineering and the performance of some selected insurance companies in Nigeria. It emphasizes the need to ensure that insurance companies achieve substantial improvement in performance via viable IT infrastructure to modernize all business processes. Design/Methodology/Approach: The study adopted a survey design, utilizing a sample of 350 respondents from two selected insurance companies in the southwest geopolitical zone of Nigeria. A questionnaire was used for the collection of data. The data analysis was conducted using the percentage formula and SPSS version 20. Findings: The research revealed that there is a significant relationship between ICT and operational performance of the insurance companies, the increase in the use of many ICT tools has proven to be caused by lockdown, which implies insurance companies should endeavor to provide updated ICT facilities to enable good quality service delivery and profitability. Technological innovations through ICT enabled the insurance industry to set up efficient delivery channels, which has capacitated the sector to solve the problems that are posed by the new change. ICT tools aided supervisors, employees, and managers in decision-making. Operational resilience became the proactive measure made by the insurance sector to ensure responsive, adaptable, and scalable services for the insured and stakeholders. Research limitation/Implication: This study exhibits practical implications for the financial service provider, as the manager and the insurer (Insurance companies) can be encouraged to find the best approach to redesign strategies and adopt basic IT facilities to automate business activities for optimal productivity and profitability. Coronavirus epidemic has created the need to emphasize the importance of making provision for a viable digital infrastructure, which ensures business continuity and customer retention, and there should be a collaboration between the financial service providers and implementing alternative delivery channels to achieve a thorough transformation that will strengthen the insurance sectors. Originality/value: This study furthers strengthens and validates the use of technology and the relevance of reengineering in operational re-enforcement for increased efficiency and effectiveness of insurance services. The improvement in business process re-engineering is driven by ICT, and as a re-engineering enabler, enhances performance that could lead to competitive advantage and a great priority for insurance companies to gain more control over the final market and good customer relationship, by offering quality services, superior value to the services, affordable price, unique customization and consultation
Keywords: D83; G22; G52; 330; Coronavirus (COVID-19); Information and Communication Technology (ICT); Insurance; Reengineering; Strategy